Effect of acetylation treatment on the physicochemical and morphological properties of three sweet potato starches (Ipomoea batatas) - TRIANA KUSUMANINGSIH; MAULIDAN FIRDAUS; DESI SUCI HANDAYANI; FYAN TRI ISTIQOMAH JUNEASRI; FAHREZA MUHAMMAD ANANTA (Society for Indonesian Biodiversity, 2023)
Abstract. Kusumaningsih T, Firdaus M, Handayani DS, Juneasri FTI, Ananta FM. 2023. Effect of acetylation treatment on the physicochemical and morphological properties of three sweet potato starches (Ipomoea batatas). Biodiversitas 24: 3038-3044. Irrespective of their promising applications, native starches still present some limitations for food industry purposes as a result of their unsatisfactory physicochemical characteristics. Nevertheless, these shortcomings can be overcome with the proper modification efforts. In this study, three different starches of sweet potatoes (white, yellow, and purple) were isolated from Ipomoea batatas (L.) Lam. have been modified by employing an acetylation reaction using acetic anhydride at concentrations of 3%, 4%, 5%, 6%, and 7%. The change in the Degree of Substitution (DS) value along with the presence of carbonyl group peaks and a decrease in the intensity of the hydroxyl group peaks after acetylation confirmed the success of the starch modification. DS showed a maximum value at 7% acetic anhydride concentration in acetate starch of 0.0492, 0.0509, and 0.0718 for white, yellow, and purple acetate sweet potatoes, respectively. The DS value of starch acetates demonstrates results that are consistent with the Food and Drug Administration (FDA) regulations (less than 2.45%), indicating that modified starches have the potential to be used in the food industry. Surface morphology analysis using the Scanning Electron Microscopy (SEM) instrument also confirmed the success of the acetylation process, where the acetylated starch surface became rougher than the original starch surface. Several physicochemical properties, including amylose, amylopectin, swelling power, water solubility, and Water Binding Capacity (WBC), were determined and showed that starch acetate has favorable characteristics for further applications in the food industry.